MAKNA KEHADIRAN IBU TUNGGAL TERHADAP PENDIDIKAN ANAK - Benny Prasetiya; Abdul Mahfud; Nur Halim; Muhaimin Muhaimin; Dina Dwi Lorenza (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
This find out about discusses the position of moms as single parents in instructing their adolescents with the condition of the living environment, which is a region of localization. Mothers who have been single dad and mom considering that their partner left them ought to play a twin position in assisting their families. The burden of mothers who have to take care of their children, earn a dwelling and educate their kids is quite heavy, many issues will be faced with the aid of mothers in educating their children, with the principal aspect being the surroundings the place the playground is a area of prostitution so that the position of the mom is like to teach their children. Based on the results of the lookup on the function of single parents in instructing their youth in the Bukit Smile localization, it can be viewed that the mother's efforts in carrying out her position as a mother with her own conditions, though there are still problems that prevent her in carrying out her function as a mother and such as lack of time to be with children, it seems that the mother continue to be accountable with their role, they nevertheless attempt to give the quality for teens and try to teach and instill accurate values and things in their children in the hope that their young people do now not get concerned with their playing surroundings and have appropriate morals